Food Truck Application in Social Computing - Talip, Bazilah A.; Haris, *, Norhaidah A. (International Journal of Engineering and Technology, 2018)
Food truck phenomenon is an emerging enterprise business that has changed people perception on particular kind of street food services. This paper discussed the influences of social computing in food truck business. Social computing is a computational system that allows contributions from both humans and computers, which can improve daily activities. Social computing enables the user to collect social information from ubiquitous environments to provide social services in web technology and mobile technology environments. The use of social computing has a significant impact on food truck business to facilitate engagement between the organisation and customers. The study aims to investigate the effect of the implementation of social computing in food truck industry. This study has developed a prototype of food truck application to demonstrate the key elements in implementing social computing. The outcomes of this study have shown that the combination of web-based and mobile technology can increase the food truck visibility and improve customer relationship. The study has shed some light on the impact of use of social computing in the food truck business to improve service delivery. The findings can assist food truck associations to better understand and provide for this emerging channel of social computing for food truck owners and customers.